Contents - Ελληνική Ψυχολογική Εταιρεία, ΕΛΨΕ (Psychology: the Journal of the Hellenic Psychological Society, 2019)
SPECIAL SECTION «PSYCHO-PEDAGOGICAL INTERVENTIONS AND PREVENTION PROGRAMS IN SCHOOLS» Invited editor: Evanthia Makri-Botsari